An audit of drug package insert: a survey based study in India - Hotha, Priyanka P.; Tanna, Purvi J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The primary source of drug information is a Package Insert. It is a printed leaflet that contains information based on regulatory guidelines for the safe and effective use of a drug. It is also known as prescription drug label or prescribing information. Regulatory requirements for drug package inserts or leaflets vary across nations. United States-Food and Drug Administration (US-FDA) and European Medicines Agency (EMA) amend their regulations governing the content and format of labelling for drug products from time to time. US-FDA has published a revised guideline in the Federal Register of January 2006, which is being followed by pharmaceutical industry of the country. Methods: Around 192 package inserts were collected from pharmacies located at different areas. They were analyzed according to Sections 6.2 and 6.3 of Schedule D of Drugs and Cosmetics Rules, 1945. Results: Out of 192 package inserts, most available information in therapeutic indications is Posology and method of administration (97.3%) followed by Contra-indications(93.2%) in pharmaceutical information, it is Special precautions for storage (77%) followed by Shelf life in the medical product as packaged for sale (33.8%). Conclusions: Contents of the package inserts should be complete, reliable and up to date. This can be a step forward for ethical and effective dissemination of healthcare services in our growing society. Therefore, recommended to update the existing package inserts based on criteria mentioned in the Schedule D of Drug and Cosmetic Act, 1945.